2012
DOI: 10.1111/j.1524-4725.2012.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Chemabrasion for Acne Scars After Treatment with Oral Isotretinoin

Abstract: Our observations may contribute to the discussion of the negative influence of oral isotretinoin on wound healing. Other studies are necessary to reevaluate the current recommendation of a 6- to 12-month waiting period after oral isotretinoin treatment before performing dermabrasion or fractional ablative laser for acne scar revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
0
24
0
5
Order By: Relevance
“…Laser light penetration is decreased in more darkly pigmented skin. Higher fluences and longer wavelengths are required to produce similar clinical effects in darker skin types but should be administered with care to prevent side‐effects caused by higher absorption of the pigmented epidermis . In darker phototypes we recommend the combined use of chilled contact gel, ice, sapphire chilled tip, cryogen spray delivered by dynamic cooling device or external air cooling to preserve the epidermis and prevent pigmentary complications.…”
Section: Treatment Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser light penetration is decreased in more darkly pigmented skin. Higher fluences and longer wavelengths are required to produce similar clinical effects in darker skin types but should be administered with care to prevent side‐effects caused by higher absorption of the pigmented epidermis . In darker phototypes we recommend the combined use of chilled contact gel, ice, sapphire chilled tip, cryogen spray delivered by dynamic cooling device or external air cooling to preserve the epidermis and prevent pigmentary complications.…”
Section: Treatment Principlesmentioning
confidence: 99%
“…30,33,34 We recommend against avoidance of laser treatment in patients who are on or have recently stopped using oral isotretinoin (GRADE 2C). [35][36][37]…”
Section: Qualification Of Providers Of Laser And/or Ipl Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Picosse et al 11 performed a prospective cohort study involving 10 patients (four women, six men), assessing outcomes after chemical peels and dermabrasion for acne scarring. All of the patients had completed treatment with isotretinoin for their acne 1-3 months previously, with a minimum accumulated dose of 122 mg kg À1 per patient.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Recently, it has been shown that laser treatment performed during or within a few months of surgical procedures significantly improves the appearance and texture of surgical scars. [12][13][14][15][16][17] The authors' aim was to evaluate the safety of ablative CO 2 fractional laser treatment of the facial area in patients with atrophic acne scars who were undergoing or had recently completed isotretinoin therapy, and to examine subsequent healing. Although clinical complications can result from fractionated laser treatment, ablative skin resurfacing with a carbon dioxide (CO 2 ) fractional laser is among the procedures that yield satisfactory results.…”
mentioning
confidence: 99%